Subject, action and polis: Theorizing political agency - Häkli, Jouni; Kallio, Kirsi Pauliina (Progress in human geography, 2014)
In this paper, we develop tools for understanding political agency and political events as they unfold contextually in everyday life. We discuss alternative understandings of the subject so as to grasp the scope of the subject’s autonomy as the ground for political subjectivity. We conceive of political agency in terms of subjectivity related to subject positions offered in the flux of everyday life. To bring together political subject and action, we conceptualize the topological settings of political agency in terms of polis. To illustrate the analytical potential of our approach, we analyse a sequence in a movie by Ingmar Bergman.